Republic of Congo : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper proposes a strategy that could mitigate the adverse effect of fiscal consolidation on inequality and poverty in the Republic of Congo. The paper reviews income inequality and poverty trend and describes the redistributive role of fiscal policy in the Republic of Congo. It also discusses how fiscal consolidation can contribute to achieving distributional objectives through tax and expenditure policy reforms. The Republic of Congo has also started implementing social safety net programs. In order to address the challenges of high poverty and inequality, the Republic of Congo government is focusing on the development of a social safety net targeted at the poor and vulnerable groups. An impact analysis carried out by the World Bank suggests that the cash transfer program could have a significant impact on poverty and inequality in the Republic of Congo. Fiscal consolidation should be based on progressive tax and spending measures, in order to protect vulnerable households during adjustment.